Razvoj mentalne reprezentacije števil v zgodnjem otroštvu - Svetina, Matija (Psihološka obzorja (Ljubljana), 2010)
Recent studies of numerosity in the field of developmental psychology indicate that numerical representation in children might be regarded in terms of Fechner's law of logarithmic relations between stimuli and response. The data also suggest that the shift from logarithmic to linear pattern of mental representation relates to different factors such as age, number scale, and culture. However, very little is known whether cognitive factors such as procedural and conceptual development have any impact on numerical representations, particularly in the preschoolers. The aim of our study was to provide an explanation of relations between numerical concepts and numerical representations in preschool children. In the study, 39 3-6 year-olds were presented with both, task of conceptual understanding of numbers and the number line task. The results indicate that the development of conceptual understanding of numbers may act as a threshold condition to the development of linear numerical representations in early childhood. Implications of these findings, such as representations of height, distance or value are further discussed.
Keywords: števila; reprezentacija; child; otroci; zgodnje otroštvo